The Euler–Mascheroni constant in school - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2014)
It is demonstrated how the Euler–Mascheroni constant $γ$ can be defined quite simple in the school. Two approaches are considered: the first one using logarithms and derivatives, and the second one using only elementary knowledge of sequences.
Keywords: Euler–Mascheroni’s constant; definitions; elementary proofs